Avaliação de fluxos de processamento para atenuação de múltiplas de superfície em dados sísmicos 2D - COSTA, Cristiane de Souza (2019)
The work was developed with the objective of applying a processing flow for the attenuation and possible elimination of multiple free surface of 2D seismic data. Were used two multiple attenuation techniques: the first technique was based on the periodicity and prediction of the multiple (SRME); and the second was based in the difference behavior between multiple and the primary on space (Radon filtering). The seismic data were processed using PROMAX package, software licensed by the company Landmark. The results were satisfactory when compared with the results obtained without the application of specific methodology.